Archaeometallurgical characterisation of Donatello's Florentine copper alloy masterpieces using portable laser-induced plasma spectroscopy and traditional techniques. (August 2015) - Siano, Salvatore; Agresti, Juri
Abstract : We investigated the execution processes and the composition of a set of well-known Florentine copper alloy masterpieces attributed to Donatello: David, San Ludovico, Pulpito della Resurrezione, Capitello, and Amore Attis . Portable laser-induced plasma spectroscopy was used in order to detect the main elements in the alloys and achieve exhaustive compositional maps of the first three works, which were executed through multiple casting and assembling. The compositions of the others were analysed using traditional techniques. The comparison of the results was extended to some celebrated masterpieces by Ghiberti and Brunelleschi, and with the information provided by documentary sources in order to achieve a preliminary picture of the alloys used by Florentine artists during the Early Renaissance.